Development of the University Anti-Fraud Disclosure Index Model as a Fraud Control System to Strengthen Integrity and Good Governance - Rahmatika, Dien Noviany; Firmansyah, Fahmi; Tri Wijaya, Juli Riyanto (Universitas Muhammadiyah Pontianak, 2025)
This study introduces the Anti-Fraud Disclosure Index (AFDi) as a new instrument for fraud control in higher education. AFDi integrates five dimensions: internal audit, integrity culture, anti-fraud socialization, transparency, and whistleblowing system. Using a Research and Development (R&D) approach with the ADDIE model, the study was limited to analysis, design, and development stages. Data were gathered through questionnaires, interviews, focus group discussions (FGDs), and expert validation, involving leaders, internal auditors, procurement officers, and lecturers from three universities in the Middle Java Province, Indonesia as a pilot project. Quantitative analysis employed non-parametric tests (Kruskal-Wallis and Mann-Whitney U Test) with Stata, while qualitative analysis used NVivo 12. Results show no significant perception differences by gender or work unit, but significant variation by respondent position. Findings stress the importance of an integrity culture, whistleblowing optimization, stronger internal supervision, and transparency. The study contributes to fraud disclosure literature and offers AFDi as a comprehensive, accountable, and sustainable fraud control model.